Valuation of sustainable attributes of hard apple cider: A best-worst choice approach. (10th October 2021) - Smith, Meghann; Lal, Pankaj; Oluoch, Sydney; Vedwan, Neeraj; Smith, Andrew
Abstract: Hard apple cider is the smallest, but fastest growing sector within the alcoholic beverage industry in the United States (US), and opens a unique opportunity for agricultural entrepreneurship amongst apple orchard owners of all sizes. To support sustainable industry development, it is important to understand which attributes of 'sustainability' are most valued by customers, and how those values translate to their willingness to pay a premium for sustainably produced goods. This study surveyed 630 hard apple cider consumers residing in the US Mid-Atlantic region. By using the best-worst choice approach, we presented a two-tiered method which estimated a hierarchal relationship among sustainability attributes that affects a cider consumer's intention to purchase at different price points. 'Local' and 'organic' held the largest utility and were both highly valued attributes, where consumers will be willing to pay a 10.05 and 6.39 premium, respectively. Agricultural management practices, 'IPM' and 'supporting biodiversity restoration, ' had a positive impact on consumer perception, and commanded a premium of 5.81 and 5.68 respectively. While 'eco-conscious packaging' and 'using renewable energy' did not show substantial utility to the consumer, respondents were still willing to pay a premium for these attributes. Social responsibility attribute levels showed negative utility, however, our analysis found that consumers were still willing to pay a premium of 5.89 for 'charitable donations' and 7.49 for 'community volunteering'. This analysis points to a key challenge in consumer behavior research: the attitude-behavior gap. Effective communication of the specific actions and inactions that take place in sustainable management practices is necessary to convey the proper message to potential consumers. By bridging this gap, hard apple cider producers can better position their product, convey important environmental information for agricultural and business management, and have consumers value their products in a way that make the additional resources allocations to incorporate sustainability metrics prudent in terms of enhanced product profitability. Highlights: Local and Organic are the most highly valued sustainability attributes of cider. Consumers are willing to pay a premium for these sustainable qualities. Multiple attributes showed a direct correlation between inherent value and WTP. Indirect correlations between value and WTP indicate an attitude-behavior gap.